A large germline deletion in the Chek2 kinase gene is associated with an increased risk of prostate cancer - Cezary Cybulski; Dominika Wokołorczyk; Tomasz Huzarski; Tomasz Byrski; Jacek Gronwald; Bohdan Górski; Tadeusz Dębniak; Bartłomiej Masojć; Anna Jakubowska; Bartłomiej Gliniewicz; A. Sikorski; Małgorzata Stawicka; et al. (2006)
Background: Germline mutations in the Chek2 kinase gene (CHEK2) have been associated with a range of cancer types. Recently, a large deletion of exons 9 and 10 of CHEK2 was identified in several unrelated patients with breast cancer of Czech or Slovak origin. The geographical and ethnic extent of this founder allele has not yet been determined. Participants and methods: We assayed for the presence of this deletion, and of three other CHEK2 founder mutations, in 1864 patients with prostate cancer and 5496 controls from Poland. Results: The deletion was detected in 24 of 5496 (0.4%) controls from the general population, and is the most common CHEK2 truncating founder allele in Polish patients. The deletion was identified in 15 of 1864 (0.8%) men with unselected prostate cancer (OR 1.9; 95% CI 0.97 to 3.5; p = 0.09) and in 4 of 249 men with familial prostate cancer (OR 3.7; 95% CI 1.3 to 10.8; p = 0.03). These ORs were similar to those associated with the other truncating mutations (IVS2+1G→A, 1100delC). Conclusion: A large deletion of exons 9 and 10 of CHEK2 confers an increased risk of prostate cancer in Polish men. The del5395 founder deletion might be present in other Slavic populations, including Ukraine, Belarus, Russia, Baltic and Balkan countries. It will be of interest to see to what extent this deletion is responsible for the burden of prostate cancer in other populations.